The Corona Virus Pandemic And Stochastic Growth: Implications For Developed, Developing, And Emerging Economies - Loubaki, Diana (European Scientific Journal, ESJ, 2021)
This article studies the impact of the â€œcoronavirusâ€ on the economy when the growth path follows a stochastic Markov process in a multi countriesâ€™ exchange context. The methodology used is endogenous growth theory coupled with topology, the fixed point, and the separation theorem for the equilibrium determination through private agentsâ€™ maximization behaviors. Thereafter, the equilibrium is rendered optimal in the Pareto sense through the linear programming method and the portfolio choice theory used by the social planner. The results found are: First, growth decreases almost everywhere; second, per-capita income increase in contrast. Finally, the conjunction of the whole accelerates convergence and catching-up since the most affected countries are also the richest. As a result, they experience higher economic and social disorders giving credibility to the Solow (1956) marginal productivity that decrease the hypothesis that poor countries grow faster than rich countries. Consequently, the pandemic negative action is an accelerator of the economic retarded countries market-based economy which targets a faster means of achievement.